Manajemen Pengembangan Pendidikan Keterampilan Anak Disabilitas Melalui Program Ticket to Life Di SLBN 2 Bantul - Murjilah, M; M, Mundilarno; Purbonuswanto, Welius (Wacana Akademika: Majalah Ilmiah Kependidikan, 2024)
This study aims to develop guidelines through analysis of skills education management for children with disabilities through the Ticket to Life (TTL) program at SLBN 2 Bantul. These guidelines/guidelines are restricted to scout teachers/coaches. Education of scouting technical skills of students with Skills need to be possessed by children with disabilities as part of children/adolescents at the age of students in general so that they are independent, confident, resilient, empowered, able to support themselves and/or others so as to achieve quality life, progress, develop, dignity, prosperity born inside. These achievements need a forum for training activities. The Asia Pacific Region (APR) Ticket to Life (TTL) program cares deeply about disadvantaged (vulnerable) children/adolescents such as disabilities, by providing skills education and elevating their dignity. Disability is one cluster that has not been addressed by Ticket To Life in the world. According to his disability, the development of motor skills of scouting techniques was chosen. The purpose of this study is to develop guidelines through the analysis of skills education management for children with disabilities through the Ticket to Life (TTL) program at SLBN 2 Bantul. These guidelines/guidelines are restricted to scout teachers/coaches. Research and Development design with development design according to Sugiyono (2009), with test subjects are principals, teachers/scout assistants/coaches, students, and the Ticket to Life team.  Data collection and analysis techniques with observation, interviews, documentation, and SWOT. The results showed that the development of these guidelines was able to make scouting skills education for children with disabilities through the Ticket to Life program at SLBN 2 Bantul effective and successful with indicators of independence, confidence, social sense and high solidarity, happy to be able to complete tasks, according to the objectives of the Ticket to Life program namely the emergence of Self Worth (gaining recognition as a human being / valued), obtaining Education (education), building Self Esteem (self-confidence), Team Spirit (spirit of togetherness), and Personal Development (self-development into responsible adults. This guide/guideline is expected to be applied to other scouting technique materials so that students master the scouting technique.